On Watching Screendance - Sherril Dodds (The International Journal of Screendance, 2019)
In this provocation, I ask what is it to watch screendance, what is at stake, and what comes into play? I suggest that in identifying works as examples of “dance on screen”, we enter into a complex history of aesthetic innovations, marketing criteria, funding systems, and intellectual debates. I compare the viewing practices of film, television and the internet, and consider how different screen formats shape experiences of teaching and research. I reflect upon the ethics of participation in online debates, and suggest that the modes and stakes of watching are as important as the dance itself.